2014
DOI: 10.1016/j.asjsur.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of albumin and synthetic polypeptide-coated oxygenators on IL-1, IL-2, IL-6, and IL-10 in open heart surgery

Abstract: Synthetic polypeptide-coated advanced technology, which employed oxygenators, had an important attenuator effect on acute phase reactants and also on the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Overexpression of IL-10 can markedly reduce the inflammatory reaction from skin damage (Peranteau et al, 2008) and can downregulate IL-6 and other pro-inflammatory factor levels (Sun et al, 2010). Some studies have showed that plasma IL-10 levels increase after major surgery (Weis et al, 2009;Simsek et al, 2013). These studies also showed that IL-6 and IL-10 are critical in tissue damage and wound healing, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…Overexpression of IL-10 can markedly reduce the inflammatory reaction from skin damage (Peranteau et al, 2008) and can downregulate IL-6 and other pro-inflammatory factor levels (Sun et al, 2010). Some studies have showed that plasma IL-10 levels increase after major surgery (Weis et al, 2009;Simsek et al, 2013). These studies also showed that IL-6 and IL-10 are critical in tissue damage and wound healing, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies showed that plasma level of IL-10 increased after major surgery. [33,34,35] The emergence of IL-10 as a key anti-inflammatory cytokine produced by Th2 cells is characterized by strong anti-inflammatory activity. [36] The overexpression of IL-10 can inhibit the release of proinflammatory cytokines, such as IL-6 and TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin and fibrinogen have been reported to be the predominant proteins to be adsorbed on vascular graft surfaces [10]. In particular, fibrinogen adsorption has been correlated with promoting 2 of 25 platelet and monocyte/macrophage adhesion, thereby leading to blood clotting [11], while albumin-coated surfaces seems to reduce leukocyte interaction, mitigating the inflammatory response [10,12].…”
Section: Introductionmentioning
confidence: 99%